Identity formation, agency, and culture : a social psychological synthesis - Côté, James E. (L. Erlbaum Associates, 2002)
This work covers topics such as psychological approaches to the concepts of self and identity, the identity concept in sociology, and the basis of a formal theory of identity formation.